Aluminosilicate glass and preparation method thereof

By using aluminosilicate glass with specific component proportions in automotive glass, the problem that existing automotive glass is difficult to meet multiple performance needs when pursuing lightweight, and the glass is lightweight, mechanical performance improvement and cost reduction are achieved.

CN116354601BActive Publication Date: 2025-03-04QINGYUAN CSG NEW ENERGY SAVING MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310400331.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2025-03-04
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

While pursuing lightweight, existing automotive glass is difficult to meet the needs of good optical performance, mechanical properties, low expansion coefficient and low softening temperature at the same time. Moreover, high-aluminum glass is difficult to produce and manufacture cost.

Method used

Aluminosilicate glasses with specific component proportions, including SiO2, Al2O3, Na2O, K2O, MgO, B2O3, ZrO2 and SnO2, were prepared with low expansion coefficient, low softening temperature, high compressive stress and compressive stress layer depth by controlling the mass percentage of these components within a specific range.

Benefits of technology

It realizes the lightweight of automotive glass, while improving the mechanical properties and chemical stability of glass, meeting the needs of automotive glass to resist impact and scratch resistance, and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004179248420000021
    Figure BDA0004179248420000021
  • Figure BDA0004179248420000022
    Figure BDA0004179248420000022
  • Figure BDA0004179248420000032
    Figure BDA0004179248420000032
Patent Text Reader

Abstract

The present invention provides an aluminosilicate glass and a preparation method thereof. The aluminosilicate glass comprises the following components by mass percentage: SiO2 60wt%-70wt%, Al2O3 8wt%-14wt%, Na2O13wt%-17wt%, K2O 1wt%-3wt%, MgO 1wt%-5wt%, B2O3 0wt%-2wt%, ZrO2 0.2wt%-3wt%, SnO2 0.2wt%-2wt%; wherein the mass percentage of Na2O is a, the mass percentage of Al2O3 is b, and 1≤a / b≤2.06 is satisfied; the mass percentage of SnO2 is x, the mass percentage of ZrO2 is y, the mass percentage of K2O is z, and 0.18≤(x+y) / z≤2.22 is satisfied. By controlling the glass components within a specific range, the aluminosilicate glass has a lower linear expansion coefficient, softening temperature and melting temperature, as well as higher compressive stress and compressive stress layer depth. Therefore, the glass thickness can be reduced and lightweight when used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of glass technology, in particular to aluminosilicate glass and a preparation method thereof. Background Art

[0002] Glass used in cars should meet many requirements. First, car glass should have good safety performance. Car glass mainly protects driving safety by ensuring vision and resisting impact. Therefore, the glass used in cars should have good optical and mechanical properties. Secondly, on the basis of basic safety performance, car glass is developing in the direction of energy saving and lightweight; lightweight car window glass can reduce the weight of the car body, save energy consumption, improve the endurance of new energy vehicles, and reduce carbon dioxide emissions.

[0003] At present, the traditional automobile windshield uses two layers of 2mm~3mm soda-lime glass to prepare laminated glass; in addition, high-aluminum glass has good mechanical strength, and one layer of high-aluminum glass less than 2mm can be used to replace the 2mm~3mm soda-lime glass in the laminated glass to achieve lightweight automobile glass; but high-aluminum production is difficult and the manufacturing cost is high. Summary of the invention

[0004] Based on this, the present invention provides an aluminosilicate glass and a preparation method thereof which meet the requirements of lightweight automobile glass and have a low expansion coefficient and softening temperature, and high compressive stress and depth of compressive stress layer.

[0005] According to a first aspect of the present invention, there is provided an aluminosilicate glass, wherein the aluminosilicate glass comprises the following components by mass percentage:

[0006]

[0007]

[0008] Wherein, the mass percentage of Na2O is a, the mass percentage of Al2O3 is b, and 1≤a / b≤2.06 is satisfied;

[0009] The mass percentage of SnO2 is x, the mass percentage of ZrO2 is y, the mass percentage of K2O is z, and 0.18≤(x+y) / z≤2.22 is satisfied.

[0010] In one embodiment, the aluminosilicate glass satisfies 1.37≤a / b≤1.77; and / or, the aluminosilicate glass satisfies 0.37≤(x+y) / z≤2.22.

[0011] In one of the embodiments, the aluminosilicate glass satisfies a / b=5; and / or, the aluminosilicate glass satisfies (x+y) / z=0.63.

[0012] In one of the embodiments, the mass percentage of ZrO2 is 0.5wt% to 2.5wt%; and / or, the mass percentage of SnO2 is 0.5wt% to 2wt%.

[0013] In one embodiment, the aluminosilicate glass further comprises the following components:

[0014]

[0015]

[0016] In one embodiment, the aluminosilicate glass comprises the following components:

[0017]

[0018] In one embodiment, the aluminosilicate glass satisfies at least one of the following conditions (1) to (3):

[0019] (1) The linear expansion coefficient of the aluminosilicate glass is 94.5×10 -7 / ℃~95×10 -7 / ℃;

[0020] (2) The softening temperature of the aluminosilicate glass is 710° C. to 743° C.;

[0021] (3) The melting temperature of the aluminosilicate glass is 1590°C to 1630°C.

[0022] According to a second aspect of the present invention, there is provided a method for preparing aluminosilicate glass, comprising the following steps:

[0023] Providing raw materials according to the above-mentioned components of the aluminosilicate glass, and mixing the raw materials to prepare a mixture;

[0024] melting the mixture to prepare molten glass;

[0025] The glass liquid is formed, and annealed and chemically toughened in sequence to obtain the aluminosilicate glass.

[0026] In one embodiment, the preparation method satisfies at least one of the following conditions:

[0027] (4) The melting temperature is 1550° C. to 1630° C., and the melting time is 6 h to 10 h;

[0028] (5) The temperature of the annealing treatment is 630°C to 700°C. The temperature of the annealing treatment is 630°C to 700°C.

[0029] (6) The aluminosilicate glass is subjected to the chemical tempering treatment in molten salt, the temperature of the chemical tempering treatment is 390° C. to 425° C., and the time of the chemical tempering treatment is 3 h to 8 h.

[0030] According to a third aspect of the present invention, a glass product is provided, comprising the aluminosilicate glass as described above or the aluminosilicate glass prepared by the method for preparing the aluminosilicate glass as described above.

[0031] Compared with the traditional technology, the present invention has the following beneficial effects:

[0032] The aluminosilicate glass of the present invention includes the above-mentioned components in specific contents, wherein SiO2 can reduce the thermal expansion coefficient of glass and enhance the strength of glass; Al2O3 can enhance the chemical stability and hardness of glass; Na2O and K2O can promote the melting of raw materials and promote chemical strengthening; MgO is beneficial to reduce the melting temperature of glass; B2O3 can reduce the softening temperature and linear expansion coefficient of glass; ZrO2 can enhance the surface hardness of glass, and SnO2 can improve the dissolution quality of glass. The above-mentioned components cooperate with each other, so that the aluminosilicate glass has a lower linear expansion coefficient, softening temperature and melting temperature, and has a higher compressive stress and compressive stress layer depth, so that the glass thickness can be reduced and lightweight can be achieved when applied.

[0033] In addition, the preparation method of the aluminosilicate glass of the present invention is simple and easy to operate. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention, etc. can be purchased from the market or can be prepared by existing methods.

[0036] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0037] In the present invention, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.

[0038] The temperature parameters in the present invention, if not specifically limited, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0039] In the present invention, % (w / w) and wt% both represent weight percentage, % (v / v) refers to volume percentage, and % (w / v) refers to mass volume percentage.

[0040] Some embodiments of the present invention provide an aluminosilicate glass, wherein the aluminosilicate glass comprises the following components by mass percentage:

[0041]

[0042]

[0043] Wherein, the mass percentage of Na2O is a, the mass percentage of Al2O3 is b, and 1≤a / b≤2.06 is satisfied;

[0044] The mass percentage of SnO2 is x, the mass percentage of ZrO2 is y, the mass percentage of K2O is z, and 0.18≤(x+y) / z≤2.22 is satisfied.

[0045] It can be understood that the value of a / b includes but is not limited to specific values ​​such as 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.06, etc.; the value of (x+y) / z includes but is not limited to specific values ​​such as 0.18, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.22, etc.

[0046] Furthermore, the aluminosilicate glass satisfies 1.5≤a / b≤1.77; further, the aluminosilicate glass satisfies a / b=1.5.

[0047] Furthermore, the aluminosilicate glass satisfies 0.63≤(x+y) / z≤2.22; further, the aluminosilicate glass satisfies (x+y) / z=0.63.

[0048] In the present invention, the mass percentage of SiO2 is "60wt% to 70wt%, which means that the minimum and maximum values ​​in the range of 60wt% to 70wt% and each value between the minimum and maximum values ​​are taken. Specifically including but not limited to the point values ​​in the embodiment and the following point values: 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt% or 70wt%; or a range composed of any two of these values, such as: 63wt% to 70wt%.

[0049] SiO2 is the main component of the glass skeleton and the largest component in the glass component. SiO2 helps to reduce the thermal expansion coefficient of the glass and improve the strength and chemical stability of the glass; when the SiO2 content is too low, the mechanical strength and weather resistance of the glass deteriorate and the thermal expansion coefficient increases; when the SiO2 content is too high, it will lead to an increase in the melting temperature, and it is easy to produce defects such as bubbles and stones, which is not conducive to industrial production; therefore, the SiO2 content in the aluminosilicate glass component of the present invention is in the range of 60wt% to 70wt%.

[0050] In some preferred embodiments, the mass percentage of SiO2 is 66wt% to 70wt%.

[0051] In the present invention, the mass percentage of Al2O3 is "8wt% to 12wt%, which means that the minimum and maximum values ​​in the range of 8wt% to 14wt% and each value between the minimum and maximum values ​​are taken. Specifically including but not limited to the point values ​​in the embodiments and the following point values: 8wt%, 8.5wt%, 9wt%, 9.2wt%, 9.5wt%, 10wt%, 10.2wt%, 10.5wt%, 11wt%, 11.3wt%, 12wt%, 12.4wt%, 12.7wt%, 13wt%, 13.5wt% or 14wt%; or a range composed of any two of these values, such as: 9.5wt% to 12wt%.

[0052] Al2O3 is beneficial to improve the structural strength of glass, promote the integrity of glass network, and enhance the chemical stability, elastic modulus and hardness of glass. 3+ The formation of glass formers [AlO4] allows for the formation of larger void channels in the network structure of the glass, which is beneficial for alkali metal ion exchange to obtain the maximum surface compressive stress (CS) and depth of layer (DOL). Therefore, in practical applications, while satisfying the same or even better mechanical effects, thick silicate glass with a smaller thickness can be used to replace thick soda-lime glass, thereby achieving lightweight automotive glass. In addition, if the Al2O3 content is too high, the viscosity of the glass will increase, the melting temperature will increase, and industrial production will be more difficult; if the Al2O3 content is too low, the ion exchange depth in chemical strengthening will be greatly reduced. Therefore, the Al2O3 range in the aluminosilicate glass component of the present invention is 8wt% to 14wt%.

[0053] In some preferred embodiments, the mass percentage of Al2O3 is 8wt% to 12wt%.

[0054] In the present invention, the mass percentage of Na2O is "13wt% to 17wt%, which means the minimum and maximum values ​​in the range of 13wt% to 17wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values: 13wt%, 13.2wt%, 13.5wt%, 14wt%, 14.2wt%, 14.8wt%, 15wt%, 15.5wt%, 16wt%, 16.2wt%, 16.5wt% or 17wt%; or a range consisting of any two of these values, such as: 14.2wt% to 16wt%.

[0055] Na2O is a network exosome that can promote the melting of glass raw materials and has a great effect on chemical strengthening. If the content of Na2O exceeds 17wt%, the weather resistance and stability of the glass will deteriorate. If it is less than 13wt%, it is not conducive to glass melting, and the strength of chemical strengthening is also reduced. Therefore, the optimal range of Na2O content in the aluminosilicate glass component of the present invention is 13wt% to 17wt%.

[0056] In the present invention, the mass percentage of K2O is "1wt% to 3wt%, which means that the minimum and maximum values ​​in the range of 1wt% to 3wt% can be taken, as well as every value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiments and the following point values: 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt% or 3wt%; or a range composed of any two of these values, such as: 1.5wt% to 3wt%.

[0057] K2O and Na2O are components with the same properties. Adding K2O and Na2O at the same time can enhance the high-temperature melting and clarification of glass and promote chemical strengthening through the mixed alkali effect. If the content of K2O is too high, the ion exchange capacity of the glass will decrease and the linear expansion coefficient will increase. Therefore, the K2O content in the aluminosilicate glass component of the present invention is in the range of 1wt% to 3wt%.

[0058] In some preferred embodiments, the mass percentage of K2O is 1.5 wt% to 2.5 wt%.

[0059] In the present invention, the mass percentage of MgO is "1wt% to 5wt%, which means that it can take the minimum and maximum values ​​in the range of 1wt% to 4wt%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values ​​in the embodiments and the following point values: 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3. 1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt% or 5wt%; or a range composed of any two of these values, such as: 2wt% to 4wt%.

[0060] MgO, as an alkaline earth metal oxide, helps to lower the melting temperature of glass, reduce the tendency of glass crystallization, and at the same time can increase the elastic modulus of glass and inhibit the generation of cracks. However, if the MgO content is too high, the linear expansion coefficient of the glass will be too high; if the MgO content is too low, the viscosity of the glass melt will increase. Therefore, the content of MgO in the aluminosilicate glass component of the present invention is 1wt% to 5wt%.

[0061] In some preferred embodiments, the mass percentage of MgO is 1 wt% to 4 wt%.

[0062] In the present invention, the mass percentage of B2O3 is "0wt% to 2wt%, which means that the minimum and maximum values ​​in the range of 0wt% to 2wt% can be taken, as well as every value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiments and the following point values: 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2wt%; or a range composed of any two of these values, such as: 0.5wt% to 1.5wt%.

[0063] B2O3 is a glass former and a solubilizing agent, which can reduce the liquidus temperature, softening temperature and linear expansion coefficient of glass, and improve the thermal properties of glass during chemical strengthening and bending forming. However, if the B2O3 content in the glass is too much, the ion exchange capacity of the glass surface will be reduced. Therefore, the content of B2O3 in the aluminosilicate glass component of the present invention is 0wt% to 2wt%.

[0064] In some preferred embodiments, the mass percentage of B2O3 is 0wt% to 1wt%.

[0065] In the present invention, the mass percentage of ZrO2 is "0.2wt% to 3wt%, " which means that the minimum and maximum values ​​in the range of 0.2wt% to 3wt% can be taken, as well as every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values ​​in the embodiments and the following point values: 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt% or 3wt%; or a range composed of any two of these values, such as: 1wt% to 2.5wt%.

[0066] ZrO2 can improve the chemical stability of glass, increase the surface hardness of glass, and resist the formation of cracks in glass and the expansion of cracks, making glass more scratch-resistant. Therefore, ZrO2 is designed as a necessary component in the glass component of the present invention. ZrO2 can also increase the ion exchange rate of glass. However, too high a ZrO2 content will significantly increase the melting temperature of glass. Therefore, the ZrO2 content in the aluminosilicate glass component of the present invention is in the range of 0.2wt% to 3wt%.

[0067] In some preferred embodiments, the mass percentage of ZrO2 is 0.5wt% to 2.5wt%.

[0068] In the present invention, the mass percentage of SnO2 is "0.2wt% to 2wt%, which means the minimum and maximum values ​​of the range of 0.2wt% to 2wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values: 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2wt%; or a range composed of any two of these values, such as: 0.5wt% to 1.5wt%.

[0069] SnO2 is used as a clarifier when the aluminosilicate glass component of the present invention is dissolved, which can reduce the gas in the glass to improve the dissolution quality of the glass. The range of SnO2 in the aluminosilicate glass component of the present invention is 0.2wt% to 2wt%.

[0070] In some preferred embodiments, the mass percentage of SnO2 is 0.5wt% to 2wt%.

[0071] The aluminosilicate of the present invention does not need to add components such as CaO and P2O5 commonly used in glass production, thereby reducing production costs.

[0072] When the mass percentage of each component in the aluminosilicate glass is controlled within a specific range and meets 1≤a / b≤2.06 and 0.18≤(x+y) / z≤2.22, the aluminosilicate glass prepared in this way can meet the requirements of automotive glass for softening temperature and expansion coefficient; at the same time, the aluminosilicate glass of the present invention has higher chemical strengthening stress and ion exchange depth, which can meet the requirements of automotive glass for impact resistance and scratch resistance.

[0073] In some preferred embodiments, the aluminosilicate glass comprises the following components:

[0074]

[0075] In one specific embodiment, the aluminosilicate glass comprises the following components:

[0076]

[0077] In some embodiments, the linear expansion coefficient of the aluminosilicate glass (30°C to 300°C) is 94.5×10 -7 / ℃~98.5×10 -7 / ℃.

[0078] In some embodiments, the softening temperature of the aluminosilicate glass is 710°C to 743°C. It is understood that the softening temperature refers to the temperature at which the glass viscosity is between 10 7.65 Temperature at dPa.s.

[0079] Furthermore, the aluminosilicate glass of the present invention has a low softening temperature and is easy to be subjected to a hot bending process.

[0080] In some embodiments, the melting temperature of the aluminosilicate glass is 1590°C to 1630°C.

[0081] In some embodiments, the compressive stress of the aluminosilicate glass is 604 MPa to 850 MPa; and the depth of the compressive stress layer is 25 μm to 40 μm.

[0082] The aluminosilicate glass prepared by controlling the glass components within a specific range has a lower linear expansion coefficient, softening temperature and melting temperature, and has higher compressive stress and compressive stress layer depth; the aluminosilicate glass of the present invention has good comprehensive properties and can meet various requirements of automotive glass.

[0083] Other embodiments of the present invention provide a method for preparing aluminosilicate glass, comprising the following steps S10 to S40.

[0084] S10, mixing the above-mentioned components of the aluminosilicate glass to prepare a mixture;

[0085] S20, melting the above mixture to prepare glass liquid;

[0086] S30, shaping the glass liquid, and sequentially performing annealing treatment and chemical tempering treatment to obtain aluminosilicate glass.

[0087] In some of the embodiments, after the melting step and before the forming step, the molten glass is further clarified and homogenized.

[0088] It is understandable that after the glass liquid is formed, its chemical composition and temperature are not uniform. In order to eliminate the non-uniformity, a homogenization treatment is required, which is usually carried out simultaneously with the clarification step.

[0089] In some embodiments, after the annealing step and before the chemical tempering step, the glass product is subjected to coarse grinding, ordinary cleaning, fine grinding, ultrasonic cleaning, CNC edge grinding and chamfering, and polishing finishing in sequence.

[0090] In some embodiments, in step S20, the melting temperature is 1550°C to 1630°C; preferably, the melting temperature is 1610°C.

[0091] In some embodiments, in step S20, the melting time is 6 hours to 10 hours.

[0092] In some embodiments, in step S30, the temperature of the annealing treatment is 630°C to 700°C; preferably, the temperature of the annealing treatment is 680°C.

[0093] In some embodiments, in step S30, the annealing treatment time is 12 hours to 24 hours.

[0094] In some embodiments, in step S30, the aluminosilicate glass is chemically tempered in molten salt; the temperature of the molten salt is 390°C to 425°C; preferably, the temperature of the chemical tempering treatment is 420°C.

[0095] In some specific examples, the molten salt is selected from molten KNO3.

[0096] In some embodiments, in step S30, the chemical toughening treatment time is 3 hours to 8 hours.

[0097] Some embodiments of the present invention further provide a glass product, comprising the above-mentioned aluminosilicate glass or aluminosilicate glass prepared by the above-mentioned method for preparing aluminosilicate glass.

[0098] The glass product has good thermal and mechanical properties and can meet the requirements of automobile glass for lightweight; the glass product can be used as automobile windshield, door glass, triangular window glass, etc.

[0099] The present invention will be further described below in conjunction with specific embodiments and comparative examples, but they should not be construed as limiting the scope of protection of the present invention.

[0100] Embodiment 1:

[0101] The aluminosilicate glass of this embodiment is prepared according to the following steps: weighing raw materials → mechanical mixing → high temperature melting → casting and molding → annealing → processing and chemical tempering → physical and chemical property testing.

[0102] Specifically, the method comprises the following steps: (1) accurately weighing the required raw materials according to the glass components shown in Table 1, a total of 800 g, and mechanically mixing for 30 minutes; (2) pouring the raw materials mixed in step (1) into a platinum-rhodium crucible, melting and keeping at 1610°C for 6 hours to 10 hours, and clarifying and homogenizing at 1610°C for 5 hours; (3) pouring the molten glass into a stainless steel mold for molding, annealing at 680°C for 10 hours, and then cooling to room temperature. The glass product is sliced ​​into 300mm*300mm*1-2mm size slices by a wire cutting machine, and then rough grinding, ordinary cleaning, fine grinding, ultrasonic cleaning, CNC grinding and chamfering, and polishing are performed. The finely processed glass slice is placed in molten KNO3 at 420°C for chemical tempering for 5 hours to obtain an aluminosilicate glass sample.

[0103] Table 1

[0104]

[0105]

[0106] The glass components of Examples 2 to 21 are shown in Table 1; other conditions are the same as those of Example 1.

[0107] Performance Testing

[0108] The performance of the aluminosilicate glasses of Examples 1 to 21 was tested as follows:

[0109] (1) The coefficient of expansion CTE (30°C to 300°C) was measured using a German NETZSCH DIL-402PC horizontal dilatometer at a heating rate of 5°C / min.

[0110] (2) The compressive stress (CS) and depth of compressive stress layer (DOL) of the glass surface after chemical tempering were measured using a FSM-6000LE surface stress meter.

[0111] (3) The strain point and softening point of glass were measured according to ASTM C-336 and ASTM C-338, respectively. The viscosity was measured by a high temperature viscometer, and the melting temperature (Tm) and softening temperature under load (Ts) were calculated by the Vogel-Fulcher-Tamann formula.

[0112] The performance test results of the aluminosilicate glasses prepared in Examples 1 to 21 are shown in Table 2.

[0113] Table 2

[0114]

[0115]

[0116] It can be seen from Examples 1 to 21 that the aluminosilicate glass prepared by using the glass components of the present application in specific mass fractions has good scratch resistance and impact resistance and can meet the performance requirements of automotive glass. Specifically, the linear expansion coefficient (30°C to 300°C) of the aluminosilicate glass of Examples 1 to 21 is 94.5×10 -7 / ℃~98.5×10 -7 / ℃, the softening temperature is 710℃~743℃ (the softening temperature in the present invention refers to the temperature when the glass viscosity is 107.65dPa.s), the melting temperature T2 is 1590℃~1630℃, the compressive stress (CS) of the glass surface after chemical tempering is 604MPa~850MPa, and the depth of the compressive stress layer (DOL) is 25μm~40μm.

[0117] The glass compositions of Comparative Examples 1 to 9 are shown in Table 3.

[0118] Table 3

[0119]

[0120]

[0121] Referring to the performance testing method of the embodiment, the performance tests were performed on the aluminosilicate glasses prepared in Comparative Examples 1 to 9. The results are shown in Table 4.

[0122] Table 4

[0123]

[0124] The difference between Comparative Example 1 and Example 17 is that the mass percentage ratio of Na2O to Al2O3 in Comparative Example 1 is less than 1, and the softening temperature and melting temperature of the aluminosilicate glass prepared thereby are higher than those in Example 17, and the chemical strengthening properties (Cs and DOL) are also slightly reduced, which increases the cost and difficulty of industrial production.

[0125] The difference between Comparative Example 2 and Example 17 is that the content of Na2O in Comparative Example 2 exceeds 17wt%, and the content of SiO2 is reduced accordingly; the linear expansion coefficient of the aluminosilicate glass prepared in Comparative Example 2 is significantly increased, and the chemical strengthening performance is also weaker than that of Example 17.

[0126] The difference between Comparative Example 3 and Example 18 is that the mass percentage ratio of Na2O to Al2O3 in Comparative Example 3 is 2.13; the compressive stress of the aluminosilicate glass prepared in Comparative Example 3 is only 490.23 MPa, the depth of the compressive stress layer is 23.45 μm, and the softening temperature is slightly higher than that of Example 18; that is, the scratch resistance of the aluminosilicate glass prepared in Comparative Example 3 is weaker than that of Example 18.

[0127] The difference between Comparative Example 4 and Example 18 is that the Al2O3 content in Comparative Example 4 is lower than 8wt%; the compressive stress and compressive stress layer depth of the aluminosilicate glass prepared thereby are significantly reduced, the thermal expansion coefficient is slightly increased, and the overall performance is weaker than that of Example 18.

[0128] The only difference between Comparative Example 5 and Example 4 is that SnO2 is not added to the glass components, the softening temperature of the aluminosilicate glass rises to 770°C, and the other properties are also weaker than those of Example 4.

[0129] The only difference between Comparative Example 6 and Example 19 is that ZrO2 is not added to the glass components, the melting temperature of the aluminosilicate glass rises to 1645°C, and the other properties are also weaker than those of Example 19.

[0130] The difference between Comparative Example 7 and Example 21 is that in the glass component, (SnO2+ZrO2) / K2O=2.46, the stress of the aluminosilicate glass is reduced to 591.59 MPa, the depth of the compressive stress layer is 29.28 μm, and other properties are also weaker than those of Example 21.

[0131] The difference between Comparative Example 8 and Example 19 is that in Comparative Example 8, (SnO2+ZrO2) / K2O=0.11, the depth of the compressive stress layer of the aluminosilicate glass is reduced to 23.14 μm, and other properties are also weaker than those of Example 19.

[0132] The difference between Comparative Example 9 and Example 8 is that in Comparative Example 9, (SnO2+ZrO2) / K2O=3.46, the compressive stress of the aluminosilicate glass is reduced to 585 MPa, the depth is reduced by 27.65 μm, and other properties are also weaker than those of Example 8.

[0133] In summary, the aluminosilicate glass using the specific components of the present application and satisfying 1≤Na2O / Al2O3≤2.06 and 0.18≤(SnO2+ZrO2) / K2O≤2.22 has excellent comprehensive properties and can meet various requirements of automotive glass.

[0134] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0135] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An aluminosilicate glass, characterized in that: The aluminosilicate glass is composed of the following components by mass percentage: Among them, the mass percentage of Na2O is a, the mass percentage of Al2O3 is b, and they satisfy 1.5≤a / b≤1.74; the mass percentage of SnO2 is x, the mass percentage of ZrO2 is y, and the mass percentage of K2O is z, and they satisfy 0.46≤(x+y) / z≤0.

63.

2. The aluminosilicate glass according to claim 1, characterized in that: The aluminosilicate glass satisfies a / b=1.

5.

3. The aluminosilicate glass according to claim 1, characterized in that: The aluminosilicate glass satisfies (x+y) / z=0.

63.

4. The aluminosilicate glass according to any one of claims 1 to 3, characterized in that: The aluminosilicate glass is composed of the following components composition:

5. The aluminosilicate glass according to any one of claims 1 to 3, characterized in that: The aluminosilicate glass satisfies at least one of the following conditions (1) to (3): (1) The linear expansion coefficient of the aluminosilicate glass is 94.5×10 -7 / ℃~98.5×10 -7 / ℃; (2) The softening temperature of the aluminosilicate glass is 710° C. to 743° C.; (3) The melting temperature of the aluminosilicate glass is 1590°C to 1630°C.

6. A method for preparing aluminosilicate glass, characterized in that: The steps include: Providing raw materials according to the components of the aluminosilicate glass according to any one of claims 1 to 5, mixing the raw materials to prepare a mixture; melting the mixture to prepare molten glass; The glass liquid is formed, and annealed and chemically toughened in sequence to obtain the aluminosilicate glass.

7. The method for preparing aluminosilicate glass according to claim 6, characterized in that: The preparation method satisfies at least one of the following conditions: (4) The melting temperature is 1550° C. to 1630° C., and the melting time is 6 h to 10 h; (5) The annealing temperature is 630° C. to 700° C., and the annealing time is 12 h to 24 h; (6) The aluminosilicate glass is subjected to the chemical tempering treatment in molten salt, the temperature of the chemical tempering treatment is 390° C. to 425° C., and the time of the chemical tempering treatment is 3 h to 8 h.

8. A glass product, characterized in that: The invention comprises the aluminosilicate glass as described in any one of claims 1 to 5 or the aluminosilicate glass prepared by the method for preparing the aluminosilicate glass as described in claim 6 or 7.

Citation Information

Patent Citations

  • Preparation method of alkali aluminosilicate glass used for protective cover plates for display parts

    CN102351421A

  • Aluminosilicate glass and tempered glass

    CN108503213A